(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to provide an introductory picture of the procedures adopted in the inventory of taxpayers in unorganized activities and to consider the ability and efficiency of these means and procedures in achieving the desired goal to enhance the financial aspect of the tax as one of the basic stages that the tax work goes through and to search appropriate ways to address the shortcomings and shortcomings، and show the importance of These procedures are in the inventory of unorganized activities، based on the importance and scope of the unorganized activities، which constitute the bulk of the taxable activity Through government support and the efforts of senior management and the role of media tools to support the tax inventory process in order to ensure that these activities are included in the tax assignment space and achieve a fair contribution to bearing public burdens and strengthening the tax resources necessary to support the development process، and therefore the research objective will be to shed light on the procedures related to inventory Those charged with unorganized activities، examining the feasibility and sufficiency of these means and procedures in achieving the desired goal، and examining appropriate ways to address the shortcomings and shortcomings therein.